Does sodium bicarbonate based extra-cellular buffering support reduce high intensity exercise-induced fatigue and enhance short-term recovery assessed by selected blood biochemical indices? - Durkalec-Michalski, Krzysztof; Kamińska, Joanna; Saunders, Bryan; Pokrywka, Andrzej; Łoniewski, Igor; Steffl, Michal; Podgórski, Tomasz (Biology of Sport, 2024)
Exercise-induced metabolic processes induce muscle acidification which contributes to a reduction in the ability to perform repeated efforts. Alkalizing agents such as sodium bicarbonate (NaHCO3) prevent large blood pH changes, however, there is no evidence on whether regulation of acid-base balance may also support whole body homeostasis monitored through heamatological and biochemical blood markers in a dose-dependent manner. Thirty Cross-Fit-trained participants were studied in a randomized, multi cross-over, placebo (PLA)-controlled double-blind manner in which they performed a control session (CTRL, without supplementation), three NaHCO3 visits (three different doses) and PLA (sodium chloride in an equimolar amount of sodium as NaHCO3). Each visit consisted of two 30-s Wingate tests separated by CrossFit-specific benchmarks (Wall Balls and Burpees – both performed for 3 min). Blood samples were collected at rest, immediately post-exercise and after 45 min recovery. Significant differences between visits appeared for blood pH, percentage of lymphocytes and granulocytes, red blood cells count and haemoglobin concentration at post-exercise and 45-min recovery, and for white blood cells count, percentage of monocytes, concentration of magnesium and creatinine at 45-min recovery. Most of the observed differences for heamatological and biochemical markers were significant compared to CTRL, but not different after PLA. NaHCO3 supplementation compared to PLA did not significantly affect exercise or recovery shifts in studied blood indicators. However, the changes in these markers after NaHCO3 and PLA in relation to CTRL indicate a possible role of sodium.